# How do you solve 5( x - 2) + x = 6( x - 4)?

Nov 10, 2016

No real solutions

#### Explanation:

distribute the five on the left side and combine like terms and distribute the six on the right side. This yields 6x-10=6x-24 which simplifies to -10=-24 which is not a true statement and therefore there are no real solutions.

Nov 10, 2016

This equation has No Solution.

#### Explanation:

First, you must simplify the two sides of the equation by applying the Distributive Property and combining like terms.

$5 \left(x - 2\right) + x = 6 \left(x - 4\right)$
$5 x - 10 + x = 6 x - 24$
$6 x - 10 = 6 x - 24$

Now that both sides of the equation are simplified, use inverse operations to solve the equation.

$6 x - 6 x - 10 = 6 x - 6 x - 24$
$- 10 = - 24$
$- 10 + 10 = - 24 + 10$
$0 \ne - 14$

Because we obtained an untrue statement when we used inverse operations to try to solve the equation for $x$. The equation has no solution. That means there is no value of $x$ which will make the equation true.